Leiomyosarcoma of the broad ligament with osteoclast-like giant cells and rhabdoid cells. - Clarke, B; Rahimi, K; Chetty, R (2010)
In this report we document an unusual co-mingling of rhabdoid and osteoclast like giant cells in a leiomyosarcoma arising from the broad ligament. A 38-year old female was found to have a rapidly enlarging adnexal mass which was resected and histologically found to be a leiomyosarcoma with marked pleomorphism. Completion surgery, shortly thereafter showed spread to the ileum, which was also resected. The tumor now showed a prominent population of both osteoclast-like giant cells and rhabdoid cells. Interestingly, the immunophenotype of the tumor had also changed with complete loss of desmin, caldesmon and only focal expression of smooth muscle actin. This is the first documentation of the coexistence of rhabdoid and osteoclast-like giant cells within a gynecological tract leiomyosarcoma. This tumor was characterized by rapid clinical progression despite extensive surgery and chemotherapy. These two cells types have individually been implicated as harbingers of a poor prognosis in leiomyosarcomas. Their prominence in the recurrent tumor and the loss of muscle marker expression are in keeping with biologic progression.